2022
DOI: 10.1302/0301-620x.104b7.bjj-2021-1771.r1
|View full text |Cite
|
Sign up to set email alerts
|

Hip dysplasia in adolescence: osteotomy in childhood improves the results of periacetabular osteotomy in adolescents and young adults

Abstract: Aims Developmental dysplasia of the hip (DDH) describes a pathological relationship between the femoral head and acetabulum. Periacetabular osteotomy (PAO) may be used to treat this condition. The aim of this study was to evaluate the results of PAO in adolescents and adults with persistent DDH. Methods Patients were divided into four groups: A, adolescents who had not undergone surgery for DDH in childhood (25 hips); B, adolescents who had undergone surgery for DDH in childhood (20 hips); C, adults with DDH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Previous studies have revealed favourable intermediate-to-long-term clinical outcomes of PAO. 14,21,22,36 Lerch et al 9 reported 88% survivorship at ten years, 61% at 20 years, and 29% at 30 years after Bernese PAO with either THA, OA progression, or Merle d’Aubigné score < 15 as the endpoint. Wells et al 10 reported 85% survivorship at ten years and 80% survivorship at 15 years after PAO, with THA as the endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed favourable intermediate-to-long-term clinical outcomes of PAO. 14,21,22,36 Lerch et al 9 reported 88% survivorship at ten years, 61% at 20 years, and 29% at 30 years after Bernese PAO with either THA, OA progression, or Merle d’Aubigné score < 15 as the endpoint. Wells et al 10 reported 85% survivorship at ten years and 80% survivorship at 15 years after PAO, with THA as the endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still very significant question marks over how and when periacetabular osteotomy should be performed, and what adjunctive treatments are needed. [21][22][23][24][25][26][27][28][29] A great deal more research is needed.…”
Section: Important Matters That Need Attentionmentioning
confidence: 99%
“…Kołodziejczyk et al evaluated the hips of adolescents who had or had not been operated on during infancy for congenital hip dislocation and the hips of adults with congenital hip dislocation during infancy who had not undergone previous surgery; they concluded that surgical treatment of congenital hip dislocation during infancy has a beneficial effect on the outcome of periacetabular osteotomies performed in adolescence and early adulthood. Particularly, Kołodziejczyk et al highlighted that the correction of radiological parameters and clinical outcome of periacetabular osteotomies were better in patients with congenital hip dislocation undergoing surgery during infancy [ 22 ].…”
Section: Introductionmentioning
confidence: 99%